Stability of Eleutherine americana (L.) Merr. Extract as Lipstick Colorants as the Change of Temperature, Time, Storage Condition and the Presence of Oxidator - Mayasari, Dewi; Rusdiana, Taofik; Ratu Kania, Yulien; Abdassah, Marline (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Bawang Tiwai (Eleutherine americana (L.) Merr bulbus. is a typical plant from Kutai tribes which commonly used as an anti-bacterial and food coloring. The stability test is performed to determine the stability of the extract. Stability test was conducted in two solvents are distilled water and ethanol include the effects of temperature (25°C, 50°C, 80°C), pH (3, 5, 7), an oxidant for 6 hours, conditions of storage at room temperature and the temperature of the refrigerator for 24 hours and storage for 2 weeks. The absorbance of extract in ethanol and aquadest was decreasing due to the change of temperature, time, the presence of oxidator but due to pH changes, the absorbance of extract was increasing. Meanwhile, on the storage condition, showed the highest absorbance on dark, and room temperature storage compared to other condition.Key words: Eleutherine americana (L.) Merr bulbus, stability, color pigment